Causes and consequences of change rates in the habitat of the threatened tropical porcupine, Sphiggurus mexicanus (Rodentia: Erethizontidae) in Oaxaca, Mexico: implications for its conservation - Lorenzo, Consuelo (Universidad de Costa Rica, 2014)
Land use changes by human activities have been the main causes of habitats and wildlife population degradation. In the Tehuantepec Isthmus in Oaxaca, the tropical habitat of the porcupine Sphiggurus mexicanus has been subject to vegetation and land use changes, causing its reduction and fragmentation.  In this study, we estimated vegetation cover and land use (dn) change rates and assessed habitat availability and potential corridors for possible porcupine movements to avoid its isolation. In the study area, the type of vegetation with the most change rate value was the savanna (dn=-2.9), transformed into induced grasslands. Additionally, we have observed the porcupine (since 2011) in semi-deciduous (dn=-0.87) and tropical dry (dn=-0.89) forests that have been transformed in temporal agriculture and mesquite and induced grasslands. The vegetation inhabited by the porcupine resulted in recording a total of 64 plant species (44 trees, nine vines, seven herbs, four shrubs), of which the vine Bunchosia lanceolata showed the highest importance value (41.85) followed by the trees Guazuma ulmifolia (22.71), Dalbergia glabra (18.05), and Enterolobium cyclocarpum (17.02). The habitat evaluation and potential corridor analysis showed that only 1 501.93ha could be considered as suitable habitats with optimum structural conditions (coverage, surface, and distances to transformed areas) to maintain viable populations of S. mexicanus, and 293.6ha as corridors. An increasing destruction of the porcupines’ habitat has been observed in the study area due to excessive logging, and actions for this species and its habitat conservation and management have to be taken urgently. Consuelo Lorenzo1*, Eugenia C. Sántiz1, Darío A. Navarrete2 & Jorge Bolaños1 1 Departamento de Conservación de la Biodiversidad, El Colegio de la Frontera Sur, Carretera Panamericana y Periférico Sur s/n. C. P. 29290. San Cristóbal de Las Casas, Chiapas, México; clorenzo@ecosur.mx, esantiz@ecosur.edu.mx, jbolanos@ecosur.mx2Laboratorio de Información Geográfica, El Colegio de la Frontera Sur, Carretera Panamericana y Periférico Sur s/n. C. P. 29290. San Cristóbal de Las Casas, Chiapas, México; dnavarrete@ecosur.mx